VD_FINDINFO Jug / 2013 / 19 vom 15. März 2013 - VD Tribunal cantonal (2013)
CONTRAT D'ARCHITECTE, DEVIS APPROXIMATIF, DILIGENCE, DÉFAUT DE LA CHOSE, HONORAIRES | 363 CO, 367 al. 1 CO, 368 al. 2 CO, 373 al. 1 CO, 394 al. 3 CO, 398 al. 2 CO